The Use of Picture Media to Improve Science Learning Outcomes in Grade V at SDN Sariwangi - Neli Nadia Adawiah; Silviana Hendri (Cv. Kilau Rashdan Publishing, 2026)
The problem addressed in this study is the low mastery of science learning in Grade V at SDN Sariwangi. Out of 35 students who took the test, only 15 students achieved mastery, while 20 students had not yet reached the mastery level. The aim of this study is to determine the improvement in science learning outcomes of Grade V students at SDN Sariwangi through the use of picture media. This research is a classroom action research (CAR) conducted in two cycles. Data were collected through tests and observations and analyzed descriptively. Data collection was carried out from November to December 2024. The subjects of this study were 35 students of class V-D. The results showed that students’ learning outcomes before the CAR were 54.2%. After the first cycle, the students’ learning outcomes remained at 54.2%. In the second cycle, the students' learning outcomes increased to 80.5%. It can be concluded that the use of picture media can improve the science learning outcomes of Grade V-D students at SDN Sariwangi. The results of this study can be used as an alternative for teachers to utilize picture media in science learning.